2020
DOI: 10.1126/sciadv.aay5064
|View full text |Cite
|
Sign up to set email alerts
|

PHOTACs enable optical control of protein degradation

Abstract: PROTACs (PROteolysis TArgeting Chimeras) are bifunctional molecules that target proteins for ubiquitylation by an E3 ligase complex and subsequent degradation by the proteasome. They have emerged as powerful tools to control the levels of specific cellular proteins. We now introduce photoswitchable PROTACs that can be activated with the spatiotemporal precision that light provides. These trifunctional molecules, which we named PHOTACs (PHOtochemically TArgeting Chimeras), consist of a ligand for an E3 ligase, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
162
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(179 citation statements)
references
References 69 publications
(89 reference statements)
1
162
0
3
Order By: Relevance
“…Studies on the cell viability of RS4;11 lymphoblast cells showed a significant difference in the activity of this protac upon irradiation with 390 nm light pulses for 72 h in comparison with incubations in the dark. These results were corroborated by a parallel light dependence degradation of the target BET proteins BRD2-4, as revealed by Western blot analysis [94].…”
Section: Photocontrolled Protacssupporting
confidence: 59%
“…Studies on the cell viability of RS4;11 lymphoblast cells showed a significant difference in the activity of this protac upon irradiation with 390 nm light pulses for 72 h in comparison with incubations in the dark. These results were corroborated by a parallel light dependence degradation of the target BET proteins BRD2-4, as revealed by Western blot analysis [94].…”
Section: Photocontrolled Protacssupporting
confidence: 59%
“…dBET6 [48], a linker optimized derivative of dBET1, showed more activities in BRD4 degradation and tumor growth inhibition in cells and mouse models of acute lymphoblastic leukemia. PROTAC-I-3 was derived from dBET1 with a light-switchable linker [49]. Upon irradiation, it robustly decreased BRD4 in leukemia RS4;11 cells and showed a potent anti-proliferation activity.…”
Section: Crbn-based Protacsmentioning
confidence: 99%
“…In addition, the Trauner group first developed a series of novel optical controlled PROTACs, named PHOTACs, for targeting FKBP12 with an azobenzene photoswitch, which inserted in the linker part of dFKBP-1 for proof of concept 338 (Fig. 48).…”
Section: Protacs For Treating Neurodegenerative Diseasementioning
confidence: 99%